IMPLEMENTASI BUDIDAYA AQUAPONIK RAKIT APUNG DALAM MEMBENTUK KARAKTER GOTONG ROYONG SISWA KELAS V SEKOLAH DASAR NEGERI POLOKARTO 3 KECAMATAN POLOKARTO KABUPATEN SUKOHARJO TAHUN AJARAN 2024/2025 - lala, andi; nugrahani, farida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this research is to describe the implementation of Floating Raft Aquaponics cultivation in fostering the spirit of mutual cooperation among fifth-grade students at Polokarto 3 Elementary School. This study employs a qualitative research design. The subjects of this research consist of all fifth-grade students at Polokarto 3 Elementary School. Data collection techniques used include interviews, observations, and documentation. Meanwhile, data analysis techniques involve data collection, data reduction, and data presentation. The data validity technique employed is triangulation. The results of the study indicate that Polokarto 3 Elementary School has implemented Floating Raft Aquaponics cultivation in developing the character of mutual cooperation within the framework of the Pancasila Student Profile Strengthening Project. This activity encourages students to collaborate, share responsibilities, and assist one another in designing, building, and maintaining the floating raft aquaponics system. Observations show an increase in collaborative attitudes and concern among students, while interviews with teachers and students indicate that this process is not only enjoyable but also reinforces values of togetherness and social responsibility. Based on the research findings, it can be concluded that the implementation of floating raft aquaponics cultivation in fostering the character of mutual cooperation is very enjoyable for students, enabling them to develop a sense of mutual cooperation independently and without coercion.